Impacts of Salinity on Soil Properties of Coastal Areas in Bangladesh - Naher, Nazmun; Uddin, M. Khabir; Alam, A.K.M.M. (AGRIVITA, Journal of Agricultural Science, 2011)
Sea level rise is a growing threat for the coastal regions of Bangladesh. It is one of the most densely populated countries of the world where 28% of the population are living in the coastal area. Bangladesh has already been affected by sea level rise through land erosion, salinity intrusion and loss in biodiversity. Saline soil has a detrimental effect upon soil physical and chemical properties. The dominant soil textural classes that occur in the saline areas of these regions are silty clay. In both of the soils pH value of the surface horizon is slightly lower than those of the subsoil and sub stratums. Cation Exchange Capacity (CEC) of all these soils varies from 12.0 to 27.6 meq/100 g soil expressing medium to high status. The organic matter content is medium to high at Asasuni and pretty low at Kalapara. In both areas, nutrient deficiencies of total nitrogen, phosphorous and potassium were quite dominant but sulphur was high. Exchangeable sodium, potassium, calcium and magnesium were in high level. The dominant water soluble cations were Na+, Ca2+, Mg2+ and K+ and anions Cl- and SO4 2-.The amount of accumulated salt was found higher at the surface and decreases with depth. Keywords : sea level rise, coastal areas, salinity, soils, flood plain